Entity Of Privacy In The Era Of Technology - RAJ, PRITHIVI; NOORANI, MURTAZA S. (The journal of contemporary issues in business and government, 2021)
The shifting sense of privacy from one social background to the next, notably in the eyes of the law, has been a persistent challenge. Technology when seen from the lens of privacy in educational institutions poses a significant threat to the safety and security of all, the most vulnerable and exposed being- young girls, female teachers with the threat of stalking and voyeurism. Furthermore, it is a flagrant breach of students' and teachers' right to privacy and freedom of speech and expression. Notably, there are no regulations or legislation in place to control the installation of surveillance and data collection devices like CCTV or other monitoring/ data collection equipment in Educational Institutes for the purposes of safety, security and regulation. The authors would also examine the above in terms of the right to privacy, necessity and legality. The authors will attempt to showcase reality on the ground along with legal landmarks to satisfy the object and rationale behind the research.